The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2001
DOI: 10.1038/sj.onc.1204948
|View full text |Cite
|
Sign up to set email alerts
|

Selective depletion of inducible HSP70 enhances immunogenicity of rat colon cancer cells

Abstract: Expression of inducible heat shock protein 70 (HSP70) in tumor cells has been proposed to enhance their immunogenicity. However, HSP70 has also been demonstrated to prevent tumor cell death, a key process for the development of tumor cell immunogenicity. In the present study, we investigated the in¯uence of the HSP70 protein level on PRO colon cancer cell growth and immunogenicity in syngeneic BDIX rats and nude mice. These cells have a basal expression of HSP70 which can be substantially increased by heat sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 48 publications
5
64
0
5
Order By: Relevance
“…Overexpression of HSP70 has been described in various tumors and has been found to be associated with enhanced tumorigenicity and resistance to therapy (2). In accordance with these findings, experimental down-regulation of HSP70 in tumor cells has been reported to enhance tumor regression in animal models (3)(4)(5).…”
supporting
confidence: 73%
“…Overexpression of HSP70 has been described in various tumors and has been found to be associated with enhanced tumorigenicity and resistance to therapy (2). In accordance with these findings, experimental down-regulation of HSP70 in tumor cells has been reported to enhance tumor regression in animal models (3)(4)(5).…”
supporting
confidence: 73%
“…Hsp70 is abundantly expressed in malignant tumors of various origins (for review, see Jäättelä 1999), and its expression correlates with increased cell proliferation, poor differentiation, lymph node metastases, and poor therapeutic outcome in human breast cancer (Ciocca et al 1993;Lazaris et al 1997;Vargas-Roig et al 1997. Furthermore, numerous experimental cancer models have demonstrated the tumorigenic potential of Hsp70 in rodents (Jäättelä 1995;Seo et al 1996;Volloch and Sherman 1999;Gurbuxani et al 2001). In support of the hypothesis that Hsp70 promotes tumorigenesis via its pro-survival function, it can effectively inhibit cell death induced by a wide range of stimuli including several cancer-related stresses like hypoxia, inflammatory cytokines, monocytes, irradiation, oxidative stress, and anticancer drugs (Jäättelä et al 1992(Jäättelä et al , 1998Jäättelä and Wissing 1993;Simon et al 1995;Mosser et al 1997;Buzzard et al 1998;Vayssier et al 1998;Nylandsted et al 2004).…”
mentioning
confidence: 83%
“…Clinical trials using a specific inhibitor of HSP90, 17-allylamino-17-demethoxygelda- namycin, are currently being performed with encouraging results (Munster et al, 2001). We and others have recently shown that downregulation of HSP70 with antisense constructs sensitizes to apoptosis induction and even can induce spontaneous cell death (Nylandsted et al, 2000;Gurbuxani et al, 2001). At least part of the cytoprotective action of HSP70 is mediated by its interaction with AIF, which does not depend on its chaperone activity.…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 overexpression has been shown to increase the tumorigenicity of cancer cells in rodent models (Jaattela, 1995). Conversely, HSP70 downregulation is sufficient to kill tumour cells or to facilitate the induction of apoptosis (Nylandsted et al, 2000;Gurbuxani et al, 2001). The antiapoptotic function of HSP70 involves interactions with several components of the apoptotic machinery.…”
Section: Introductionmentioning
confidence: 99%